Attachment trauma and role of secure base in selected literary works of black women writers - Dodhy, Shamaila (2018)
Most research in the field of trauma studies has been limited to the sufferings of Whites, focusing predominantly on the agonies of Holocaust victims and repercussions of military operations on war veterans. Some researchers have examined victimization of black women in light of Trauma Studies with reference to slavery, racism, colonialism and the concept of beauty but my research will strive to focus on those fictional characters who suffered from attachment trauma. These characters are perpetrated by their close relations who are supposed to protect them and safeguard their rights. Traumatic experiences of these characters by their familymembers result in psychological disorders. This aspect has hardly been explored. I intend to fill the gap by examining contemporary African and African-American literature produced by black women in the light of Jon G. Allen’s Attachment Trauma Theory. This study seeks to analyze the fictional works of Yvonne Vera’s Under the Tongue (1996), Toni Morrison’s Paradise (1997), Zelda Lockhart’s Fifth Born (2010), and Yejide Kilanko’s Daughters Who Walk This Path (2012). The study aims to examine the silenced characters that have experienced not only physical intrusion but also substantial psychological and emotional trauma. I aim to explore how attachment trauma and attachment anxiety are related to emotional damage of these characters. Life becomes frightful as one has to survive in intimidating domestic environment with lingering traumatic memories. In this study, the role of secure base will also be identified as a means of recovering the shattered selves of the characters. This research will evaluate if affectionate and caring attachment figures have comforting, healing and therapeutic effects on the suffering individuals. These individuals struggle to achieve integrity and independence while coping with humiliation and loneliness. This Trauma Fiction conveys traumatic knowledge using stylistic features where the concept of time freezes like the experience of trauma. These pain narratives authenticate female resistance against violent patriarchal structures of the social order.